Role of Inflow of Resources on Economic Growth of Nepal - Mahara, Tilak Singh; Bhatt, Naw Raj (Economic Journal of Nepal, 2019)
This study attempts to examine the role of the inflow of resources on the economic growth of Nepal incorporating annual time-series data sets of 45 years from 1975 to 2019. The autoregressive distributed lag approach to cointegration is used to identify the long-run as well as the short-run relationship between the variables. The empirical finding indicates that there is a positive relationship between the inflow of resources and economic growth. Quantitatively, gross national saving, domestic loans, foreign loans, and export earnings have a positive impact on the economic growth in both the long-run as well as short-run for the Nepalese economy. Policies encouraging private sector participation, enlarging efficiency, and effectiveness of public sector projects, and expanding export base must be implemented.